The Influence of K3, Motivation, and Job Satisfaction on Employee Performance at PT Pertamina (Persero) - Sabilla, Fahira Nur; Chodidjah, Suryani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to determine the effect of HSSE (Health, Safety, Security, and Environment), motivation, and job satisfaction on employee performance at PT Pertamina. The approach used is quantitative with 144 employees as respondents. Data collection was carried out through questionnaires, and data analysis using SPSS version 25. The results of the analysis showed that the HSSE and motivation variables had a significant effect on employee performance, while job satisfaction did not have a significant effect. These findings indicate that the implementation of a good work safety program and increased motivation through incentives, recognition, and career development opportunities have an important contribution to improving performance. Meanwhile, job satisfaction does not directly affect performance, but remains relevant to other aspects such as loyalty and retention. Therefore, PT Pertamina needs to focus its human resource management strategy on strengthening the HSSE system and work motivation in order to create optimal and sustainable performance in a competitive oil and gas industry environment.